DIMENSIONS OF COMPULSIVE OPTIMISM: A HUMANISTIC EXISTENTIAL REFLECTION (CIPEEX, 2026)
Introduction: Compulsive optimism, also referred to in the literature by synonyms such as toxic positivity and unrealistic optimism, represents a practice of devaluing negative experiences and feelings relevant to human psychological health. Objective: To examine and address compulsive optimism through the lens of the existential humanistic approach. Method: Analysis of compulsive optimism in three dimensions: the denial of negative emotions, the attribution of blame to conduct, and the certainty of success. For this purpose, reflections are developed in dialogue with authors and texts related to the approach as theoretical support. Results: Identification of negative experiences and emotions as a natural human condition, which can be used for growth. Conclusions: A scarcity of recent studies on the topic was observed, especially in quantitative research, highlighting the importance of increasing initiatives in this context for deeper theoretical development.
Keywords: optimism; happiness; existentialism; humanism